Clomiphene Citrate versus Clomiphene Citrate in combination with other drugs in Ovulation Induction in Patients with Polycystic Ovary Syndrome - Mostafa Khodary; Yasser Ahmed Abuelwafa Abdellatif; Mahmoud Ibrahim Almolakab B- Alrashidy; Sayed Ahmed Mohammed Taha (SVU - International Journal of Medical Sciences, 2025)
Background: Polycystic ovary syndrome (PCOS) is the most prevalent cause of normogonadotrophic anovulation, also classified as World Health Organization group II anovulation. Objectives: The aim of this study was to compare the effectiveness and clinical outcomes of clomiphene citrate alone and with different combinations (metformin , tamoxifen , letrozole and low dose gonadotrophins ) in induction of ovulation in women with PCOS. Patients and methods: The Obstetrics and Gynecology department at Qena University Hospital, South Valley University, was the site of this randomized study. The study included 400 infertile cases with PCOS divided on 5 groups . The duration of the study ranged from 12-24 months. Results: In the studied groups, group 4 (clomiphene and letrozole ) and group 5 (clomiphene and low dose gonadotrophins) had the highest ovulation rate which was 31.3 % , 41.3 % respectively and also the highest pregnancy rate which was 33.8 % for each group . Conclusion: The combination of clomiphene and letrozole and clomiphene and gonadotrophins had proved to be the most effective , low cost infertility treatment in women with PCOS that offers high ovulation and pregnancy rates.